Conceptual Approaches to Implementing the Digital Supply Chain Management in Some Areas of the Russian Economy - A.V. Kolesnikov; O.V., Chumakova; S. Yu. Syvorotkina; E.S. Karsanova; T.V. Skoblikova (International Journal of Supply Chain Management, 2020)
Abstract— Recently, digital, information and telecommunications resources have become widespread in Russia, and the processes of supply chain in various spheres of society are being actively digitized after the covid-19 spread. As of today, there is a successful experience in the development and subsequent use of various electronic platforms, systems and services, such as SIS of HCS (in the field of housing and communal services), UMIAS (healthcare), Public Services (provision of public services), UIS (procurement), etc. The existence of such software products affects effectively the performance of functions by public authorities, allows optimizing the work, and also provides access to the necessary information. Based on this, we can say that digital technologies cover most areas of the country’s life. However, these areas of activity are usually not related to production. This situation is developing not only in Russia, but also in the global economy as a whole. It is easy to implement digital technologies in the service sector. This is largely due to low-cost investments that pay off quickly and make services more affordable. This is not the case with production, where the introduction of digital technologies will require changing the technology or even the organizational mechanism of production functioning. Moreover, it does not depend on which sector of the economy will be affected by the introduction of digital supply chain management (DSCM). The tasks of digital technologies in production should be a significant increase in labor productivity, the use of modern technologies that allow competing in the world market of goods. In addition, digital technologies in the manufacturing sector of the economy are designed to facilitate production management, correct management decisions, and obtaining detailed, necessary information about production processes.